2021
DOI: 10.3389/fimmu.2021.646304
|View full text |Cite
|
Sign up to set email alerts
|

STING Operation at the ER/Golgi Interface

Abstract: DNA is present in the nucleus and mitochondria of eukaryotic cells. There are, however, certain instances in which DNA emerges in the cytosol. The two major sources of cytosolic DNA are self DNA that is leaked out from the nucleus or mitochondria, and non-self DNA from DNA viruses. The cytosolic DNA triggers the host immune response. Recent studies have identified two key molecules, cyclic GMP-AMP (cGAMP) synthase (cGAS) and stimulator of interferon genes (STING) in this immune response. STING is an endoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 62 publications
(86 reference statements)
1
52
0
Order By: Relevance
“…Activated STING stimulated type I IFN-driven inflammation in COPA model mice that was rescued in STING-deficient animals. Also, STING deficiency reversed the significant increase of activated effector T cells caused by mutant COPA ( 12 , 94 , 95 ). These results suggested that STING played a key role in COPA mutation-induced immune disorders, mainly by promoting the differentiation of effector T cells, which indicated that we could develop effective STING pathway inhibitors to treat COPA symptoms.…”
Section: Autoimmune and Inflammatory Diseasesmentioning
confidence: 91%
“…Activated STING stimulated type I IFN-driven inflammation in COPA model mice that was rescued in STING-deficient animals. Also, STING deficiency reversed the significant increase of activated effector T cells caused by mutant COPA ( 12 , 94 , 95 ). These results suggested that STING played a key role in COPA mutation-induced immune disorders, mainly by promoting the differentiation of effector T cells, which indicated that we could develop effective STING pathway inhibitors to treat COPA symptoms.…”
Section: Autoimmune and Inflammatory Diseasesmentioning
confidence: 91%
“…But pulmonary inflammation plays differential roles in COPA and SAVI ( 11 ). Recent reports show that a defect in COPI transport causes ligand-independent activation of STING and COPA maintains immune homeostasis by regulating STING transport at the Golgi ( 3 , 4 , 12 ). These findings tell the link between COPA mutants and STING-mediated interferon signaling ( 3 , 4 , 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports show that a defect in COPI transport causes ligand-independent activation of STING and COPA maintains immune homeostasis by regulating STING transport at the Golgi ( 3 , 4 , 12 ). These findings tell the link between COPA mutants and STING-mediated interferon signaling ( 3 , 4 , 12 , 13 ). The expression of COPA mutants enables STING to accumulate in the Golgi, whereas COPA overexpression does not affect the localization of STING in the ER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The membrane transport of STING is co-mediated by COP-II and COP-I. Thus, using the regulatory agents to target membrane transport is likely to be a novel strategy for treating autoimmune diseases ( Taguchi et al, 2021 ). However, the regulatory factors of STING transfer from the Golgi apparatus to the lysosome and the mechanisms of STING, NF-κB, and autophagy remain to be further studied.…”
Section: Summary and Prospectmentioning
confidence: 99%